2012
DOI: 10.1177/0038038511422553
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Sociological Understanding of Social Media: Theorizing Twitter

Abstract: This article presents the first steps towards a sociological understanding of emergent social media. This article uses Twitter, the most popular social media website, as its focus. Recently, the social media site has been prominently associated with social movements in Libya, Egypt, Tunisia, and Algeria. Rather than rush to breathlessly describe its novel role in shaping contemporary social movements, this article takes a step back and considers Twitter in historical and broad sociological terms. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
206
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(228 citation statements)
references
References 28 publications
3
206
0
19
Order By: Relevance
“…Poole's arguments share some commonality with many of the studies that have applied Goffman's theories of the presentation of self to social media sites (see Marwick and boyd, 2011;Murthy, 2012;Livingstone, 2008;van Dijck, 2013;Vitak, 2012). These articles tend to analyse impression management online as a practice rather than the representation of a "true" static identity.…”
Section: Beyond the 'Anonymity Continuum'mentioning
confidence: 88%
“…Poole's arguments share some commonality with many of the studies that have applied Goffman's theories of the presentation of self to social media sites (see Marwick and boyd, 2011;Murthy, 2012;Livingstone, 2008;van Dijck, 2013;Vitak, 2012). These articles tend to analyse impression management online as a practice rather than the representation of a "true" static identity.…”
Section: Beyond the 'Anonymity Continuum'mentioning
confidence: 88%
“…Murthy (2012) has suggested that having a conversation on Twitter can be like sitting in a room not knowing who is going to appear through the door, or indeed who is listening behind it. This, he argues, is consistent with the main purpose of Twitter being to publish content rather than foster networks.…”
Section: Extractmentioning
confidence: 99%
“…The transmission of messages, or 'tweets', is conducted from an individual's Twitter account where the user has the option to create their own profile through the use of a Twitter address or a 'handle' and a biographical description with a photograph and some personal background information (Murthy 2012(Murthy :1059Qiu, Lin, Ramsay & Yang 2012:710). Naturally, all these variable factors provide the constituents for an exceptionally dynamic interaction leading to the following possibility:…”
Section: What Is Going On? Twitter and A Digital Worldmentioning
confidence: 99%